Islamic Education Model for Muallaf (Converts) through a Participatory Approach - Marhamah Marhamah; Hidayati Hidayati; Rezki Amelia; Gusmirawati Gusmirawati; Radhiatul Hasnah (AT-TA'LIM, 2022)
The purpose of this research is to develop a model of Islamic religion studies for converts by using a participatory approach. This is intended to provide an understanding that converts need directions and guidances. It is not only in order to deepen understanding or increase confidence, but also concerns about their existence as converts. Based on the interviews conducted, it is known that converts need a forum as a place to continue in understanding the religion of Islam. Thus, the development of a model of Islamic studies education for converts is very urgent to do. This study used a qualitative research method by using a descriptive analysis approach. The results showed that the model of converting to Islam which was developed in a participatory approach was adapted to the needs of converts themselves. In this case, the researcher designs the needs of converts by translating and describing the expressions of converts into a framework to become an educational model.